The use of the Callan method in maritime English teaching - Yurzhenko, Alona; Kononova, Olena; Diahyleva, Olena (Educational Challenges, 2025)
The purpose of this article is to analyse the use of the Callan method in teaching Maritime English to today’s future ship engineers, in the context of e-learning. Our hypothesis is that online classes can successfully be used to implement the Callan Method in Maritime English for both teaching and learning. Methodology. This study employed a quasi-experimental pedagogical research design to evaluate the effectiveness of an online learning approach in Maritime English training at the Kherson State Maritime Academy (KhSMA). A mixed-methods approach was used, combining quantitative analysis of test results and oral competence assessments with qualitative insights from teacher observations. The course implemented the Callan Method to develop all four language skills – listening, reading, writing, and speaking – and interactive online activities formed part of the learning process. Cadets’ oral communicative competence was assessed through programmed online speaking tasks conducted via video conferencing tools. Teacher feedback and analysis of cadet participation in online discussions, quizzes, and speaking activities were used to provide a comprehensive evaluation of the outcomes of this online-only learning model. Results: The pedagogical experiment at KSMA showed that group 211ap, which used the Callan Method for Maritime English, achieved significantly higher results in comparison to the control group (212ap). In 211ap, none of the cadets were deemed to have reached a ‘satisfactory’ level only, whilst the number of those who achieved a ‘very good’ or ‘excellent’ level increased, including 11 cadets who were deemed ‘excellent’. Previous to this experiment, none of the cadets had reached this level of competence. The control group, who were taught using traditional methods, were also found to have improved, but to a lesser degree: seven additional cadets reached a ‘good’ or ‘very good’ level, whilst one cadet was deemed ‘excellent’. Overall, the findings confirm the Callan Method’s effectiveness in enhancing communicative competence in Maritime English for future ship engineers. Conclusions: Maritime English is essential for the professional development of future seafarers, and in particular, for marine engineers. The Callan Method has proven effective in providing a greater number of opportunities for speaking practice than traditional approaches, particularly with regard to SMCP and simulated radio communication. It promotes rapid speaking and automates language structures and marine terms, making it highly suitable for ship engineers. However, it was also found to have some disadvantages, such as limiting learners’ creativity. Low level of motivation amongst cadets learning maritime English was also a noted tendency, as a result of the format of the exercises themselves. Notwithstanding levels of motivation, these same exercises were also noted to be of great help in learning maritime English. Future research could explore its application for training ship navigators and electrical engineers.